2013
DOI: 10.1177/0003319713487428
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cardiovascular Risk Factors Between Patients With Acute Limb Ischemia and Intermittent Claudication

Abstract: In this retrospective study, cardiovascular risk factors of patients with acute limb ischemia (ALI) were compared with those of intermittent claudication (IC). Furthermore, the association of ALI with environmental temperature and/or hematocrit level was tested. A total of 436 patients treated for ALI and 832 patients with IC were included in the analysis. Diabetes (P = .0001), smoking (P < .0001), and hypertension (P < .0001) were significantly less prevalent in the patients with ALI. Patients with IC had a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…Since ALI is a drastic event for patients, their adherence to medication and control of cardiovascular risk factors might be better and explain, at least in part the low rate of events. Furthermore, ALI patients are significantly less often diabetics and smokers compared to patients presenting with intermittent claudication and might therefore have a smaller burden of generalised atherosclerosis, as recently reported by our group [6].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Since ALI is a drastic event for patients, their adherence to medication and control of cardiovascular risk factors might be better and explain, at least in part the low rate of events. Furthermore, ALI patients are significantly less often diabetics and smokers compared to patients presenting with intermittent claudication and might therefore have a smaller burden of generalised atherosclerosis, as recently reported by our group [6].…”
Section: Discussionsupporting
confidence: 72%
“…The reported short-term mortality of patients presenting with ALI was about 15 % to 20 %, depending on the outcome of the acute phase and comorbidities [5]. In a recent study, we compared claudicants and patients with ALI regarding cardiovascular risk factors [6]. We found that smoking, diabetes and coronary artery disease (CAD) are less prevalent in patients with ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new approaches have also been tried: surgical treatment, such as percutaneous transluminal angioplasty (PTA) and revascularization; [8][9][10][11] use of autologous, stem and embryogenic cells for critical limb ischemia; 12,13 mixed surgical and pharmacological intervention, such as drug-eluting balloons; 8,14,15 new resorbable stent; 16 or promising extracorporeal shockwave therapy (ESW). 17 Medical treatments used for cardiovascular risk control, such as statins, might slightly contribute to ICD improvement.…”
Section: Introductionmentioning
confidence: 99%
“…CAD is reported to be concomitant in approx. About 40% to 80% of PAD patients with intermittent claudication . In this context it is of particular importance that PAD on its part is associated with increased severity of CAD as indicated by higher rate of multivessel and left main CAD .…”
Section: Introductionmentioning
confidence: 99%
“…About 40% to 80% of PAD patients with intermittent claudication. 16,17 In this context it is of particular importance that PAD on its part is associated with increased severity of CAD as indicated by higher rate of multivessel and left main CAD. 18,19 Heart failure is therefore more common in PAD and reduced left ventricular ejection fraction increased risk of major cardiovascular events in patients with intermittent claudication.…”
Section: Introductionmentioning
confidence: 99%